Modified nano copper oxide lubricating oil with high thermal conductivity and preparation method thereof

Nano-oxide copper lubricant modified by silane coupling agent solves the problem of insufficient cooling performance of traditional lubricants under low speed, heavy load and high temperature conditions, achieves high thermal conductivity and stable heat dissipation performance, effectively controls the watt temperature, and improves the reliability of the water turbine generator set.

CN119899711APending Publication Date: 2025-04-29SANXIA JINSHAJIANG YUNCHUAN HYDROPOWER DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411816622.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing lubricating oil is limited in the lubricating and cooling functions under low speed, heavy load and high temperature conditions, resulting in insufficient cooling performance of the thrust bearing of the water turbine generator, which is prone to high watt temperature.

Method used

Nanocopper oxide modified with silane coupling agent was prepared by ultrasonic dispersion and magnetic stirring and other processes to prepare a modified nanocopper oxide lubricating oil with high thermal conductivity. The lubricating oil is dispersed and stable in the base liquid, has a higher thermal conductivity, and can improve the heat dissipation performance of the thrust bearing.

Benefits of technology

The thermal conductivity of modified nano-oxide copper lubricating oil is significantly improved, which can effectively control the wall temperature of the thrust bearings, improve the reliability and stability of the hydrowheel generator set, and meet the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899711A_ABST
    Figure CN119899711A_ABST
Patent Text Reader

Abstract

The invention discloses high-thermal-conductivity modified nano copper oxide lubricating oil and a preparation method thereof, the high-thermal-conductivity modified nano copper oxide lubricating oil comprises a silane coupling agent modified nano copper oxide additive and lubricating oil, and the silane coupling agent is gamma-methacryloxypropyltrimethoxysilane. The surface of the nano copper oxide is modified by adopting the silane coupling agent, and after the nano copper oxide is added into lubricating oil as an additive, the dispersion stability of the nano copper oxide in a lubricating oil base solution is improved, so that the thermal conductivity of the lubricating oil is improved, the nano copper oxide is used for effective heat dissipation of a thrust bearing of a water-turbine generator set, and the temperature of a thrust bearing bush is controlled at a lower level. The preparation process is simple, the selected modifier is wide in source and low in price, and the prepared lubricating oil is environmentally friendly and meets the requirement of sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating oils, and in particular relates to a modified nano copper oxide lubricating oil with high thermal conductivity for a hydraulic generator thrust bearing and a preparation method thereof. Background Art

[0002] Thrust bearings are important components of hydro-turbine generator sets. They mainly bear the total weight of the rotating parts of the unit and the axial water thrust. The quality of their working performance directly affects whether the hydro-turbine generator set can operate long-term, safely, stably and reliably. According to relevant data, the reliability of thrust bearings in large hydro-turbine generator sets is low. 55-70% of the mechanical equipment failures of hydraulic units are caused by thrust bearings, and the manifestation of failures is high temperature or burning of bearings. The thrust bearing oil tank is filled with lubricating oil. Under normal circumstances, the heat lost in the lubricating oil by the thrust bearing during its operation is dissipated through the flow of lubricating oil, thereby ensuring that the bearing temperature is maintained within the normal temperature threshold. Therefore, the thrust bearing oil circulation cooling system is the key to ensuring the safe and reliable operation of the bearing. With the continuous advancement of my country's hydropower technology and the increasing application of large and giant hydro-turbine generator sets, how to improve the cooling performance of the thrust bearing oil circulation cooling system is becoming increasingly important.

[0003] Lubricating oil is a high-viscosity, low-thermal-conductivity fluid with limited heat exchange capacity. Especially under low-speed, heavy-load, and high-temperature conditions, its lubrication and cooling functions will be greatly limited. Therefore, it is a new idea to develop a new type of lubricating oil with high heat transfer performance, high thermal conductivity, and excellent performance to replace traditional lubricating oil in order to achieve a better cooling effect for thrust bearings. Nanoparticles have the characteristics of high specific surface area and low melting point. The nanofluids made from them have special properties such as low pressure drop, high thermal conductivity, and high cooling capacity, thereby achieving the purpose of enhancing the thermal properties of the base fluid and strengthening the heat transfer performance. However, nanoparticles are easy to agglomerate in the base fluid, resulting in low thermal conductivity of the nanofluid. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a modified nano copper oxide lubricating oil with high thermal conductivity.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0008] Lubricating oil base fluid, and

[0009] Compared with the nano copper oxide modified by silane coupling agent with the usage of lubricating oil base fluid of 0.05-0.5%;

[0010] Wherein, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the mass ratio of the silane coupling agent to the nano copper oxide is 5 to 1:1.

[0011] As a preferred solution of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the mass ratio of the silane coupling agent to the nano copper oxide is 5:1.

[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a modified nano copper oxide lubricating oil with high thermal conductivity.

[0013] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0014] Nano-copper oxide is ultrasonically dispersed in distilled water to obtain a nano-copper oxide suspension;

[0015] The silane coupling agent is dissolved in isopropanol to obtain a silane coupling agent solution;

[0016] The nano copper oxide suspension is added to the silane coupling agent solution to obtain a mixed solution, and the mixed solution is heated, stirred, centrifuged, washed, and dried to obtain nano copper oxide powder modified by the silane coupling agent;

[0017] The nano copper oxide powder modified by silane coupling agent is added into the lubricating oil base liquid, and the modified nano copper oxide lubricating oil with high thermal conductivity is obtained through ultrasonic dispersion and magnetic stirring.

[0018] As a preferred embodiment of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the temperature for heating and stirring the mixed solution is 60-80° C. and the stirring time is 30-50 min.

[0019] As a preferred solution of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the mixed solution is centrifuged at a speed of 5000 to 9000 rpm for 5 to 15 minutes.

[0020] As a preferred solution of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the washing is performed 3 to 5 times.

[0021] As a preferred embodiment of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the drying temperature is 60 to 80° C. and the drying time is 16 to 24 hours.

[0022] As a preferred solution of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the ultrasonic time after the modified nano copper oxide is added into the lubricating oil is 10 to 15 minutes.

[0023] As a preferred solution of the method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity described in the present invention, the magnetic stirring speed is 900-1000 rpm, and the stirring time is 2-4 hours.

[0024] Another object of the present invention is to overcome the deficiencies in the prior art and provide a modified nano copper oxide lubricant with high thermal conductivity for use in a hydraulic generator thrust bearing.

[0025] Beneficial effects of the present invention:

[0026] (1) The modified nano copper oxide prepared by the present invention is not easy to agglomerate in the base liquid and has good dispersion stability. In addition, the preparation process of the modified nano copper oxide is simple, the source of the modifier is wide, and the price is low;

[0027] (2) The thermal conductivity of the modified nano copper oxide lubricating oil prepared by the present invention is higher than that of the unmodified nano copper oxide lubricating oil, which can improve the heat dissipation performance of the lubricating oil in the thrust bearing of the hydro-turbine generator set and effectively control the bearing temperature from being too high;

[0028] (3) The nanofluid prepared by using modified copper oxide in the present invention will not cause pollution to the environment and meets the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 This is a comparison chart of the dispersibility of lubricating oils prepared using different nanoparticles in the present invention;

[0031] Figure 2 This is a stability diagram of the lubricating oil system prepared by mixing CuO with four dispersants respectively in the present invention;

[0032] Figure 3 The present invention adopts Al 2 O3 Stability diagram of lubricating oil systems prepared by mixing with four dispersants;

[0033] Figure 4 The present invention uses SiO 2 Stability diagram of lubricating oil systems prepared by mixing with four dispersants;

[0034] Figure 5 The present invention uses Fe 3 O 4 Stability diagram of lubricating oil systems prepared by mixing with four dispersants;

[0035] Figure 6 The scanning electron microscope (SEM) images of the nano copper oxide used in Example 1 of the present invention and the prepared modified nano copper oxide;

[0036] Figure 7 Fourier transform infrared spectra of nano copper oxide and KH570 used in Example 1 of the present invention and the prepared modified nano copper oxide;

[0037] Figure 8 X-ray diffraction (XRD) diagrams of the nano copper oxide used in Example 1 of the present invention and the prepared modified nano copper oxide;

[0038] Fig. 9 Fourier transform infrared images of KH570 and nano copper oxide used in Comparative Example 1 of the present invention and the prepared modified nano copper oxide;

[0039] Fig.10 Thermogravimetric analysis diagrams of the nano copper oxide used in Examples 1 to 5 of the present invention and the prepared modified nano copper oxide;

[0040] Fig.11 The grafting rate diagram of the surface of modified nano copper oxide prepared in Examples 1 to 5 of the present invention and Comparative Example 1;

[0041] Fig.12 This is a flow chart of the preparation of nano copper oxide lubricating oil in Comparative Example 2 of the present invention;

[0042] Fig.13 The thermal conductivity curves of the lubricating oils prepared in Examples 1 to 5 of the present invention and Comparative Example 1 at different temperatures;

[0043] Fig.14 Thermogravimetric analysis diagrams of nano copper oxide used in Comparative Example 3 of the present invention and APTES-modified nano copper oxide prepared;

[0044] Fig.15X-ray diffraction (XRD) patterns of nano copper oxide used in Comparative Example 3 of the present invention and APTES-modified nano copper oxide prepared with a mass ratio of APTES to nano copper oxide of 5:1;

[0045] Fig.16 Fourier transform infrared spectra of nano copper oxide and APTES used in Comparative Example 3 of the present invention and APTES-modified nano copper oxide prepared with a mass ratio of APTES to nano copper oxide of 5:1;

[0046] Fig.17 This is the thermogravimetric analysis diagram of KH570 modified nano copper oxide prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0049] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0050] The conventional lubricating oil used in the present invention is L-TSA46, and its kinematic viscosity is 46.05 mm 2 / s, viscosity index is 106, pour point is -9℃, flash point is 239℃, density is 871kg / m 3 .

[0051] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0052] The present invention adopts a thermal constant analyzer to measure the thermal conductivity of the nanofluid, and simultaneously obtains the thermal conductivity of the material at different temperatures through a transient plane source technology.

[0053] The present invention selects SiO 2 、Al 2 O 3 Three different nanoparticles of CuO were added to the lubricating oil without adding dispersant. The dispersibility of the nanoparticles in the lubricating oil was observed. The results are as follows Figure 1As shown in Figure 1, (a) and (b) are the dispersion of nanoparticles after 3 and 7 days of standing, respectively. It can be clearly seen from the figure that after 3 days of standing, CuO has the best dispersion, while SiO 2 and Al 2 O 3 After 7 days of standing, CuO precipitated but was still partially suspended, while SiO 2 and Al 2 O 3 It can be seen that CuO has the best dispersibility in the lubricating oil base fluid. Based on this, the present invention initially selects CuO as an additive to prepare lubricating oil.

[0054] In order to further determine the effect of CuO nanoparticles on the stability of lubricating oil, the present invention selects CuO, Al 2 O 3 , Fe 3 O 4 and SiO 2 , respectively mixed with four dispersants PVP, SDS, SDBS, and sodium citrate at a mass ratio of 1:1 to prepare lubricating oil. The prepared lubricating oil was centrifuged at a speed of 150r / min for 15min, 30min, 60min, 120min, and 180min. After each centrifugation, the upper layer of liquid was taken and the transmittance was measured using an ultraviolet spectrometer. The results are as follows Figures 2 to 5 shown.

[0055] Figure 2 The following are the results of centrifugation treatment for different time periods for lubricating oils prepared by mixing CuO with four dispersants. It can be seen that precipitation appeared at the bottom when the centrifugation time was 120 minutes, and the precipitation at the bottom increased at 180 minutes. In addition, as the centrifugation time increased, the transmittance of the CuO lubricating oils with different dispersants did not change much, indicating that the sedimentation of CuO particles was not obvious and the CuO lubricating oil system was relatively stable.

[0056] Figures 3 to 5 Al 2 O 3 、SiO 2 and Fe 3 O 4 The results of centrifugation treatment of lubricating oils mixed with four dispersants for different times. Figure 3 It can be seen that for Al 2 O 3 Although there was no obvious precipitation at the bottom after centrifugation for 180 min, the addition of different dispersants to Al 2 O 3 The lubricating oil permeability changes greatly, indicating that Al 2 O 3Particle sedimentation is obvious, Al 2 O 3 The lubricating oil system is unstable. Figure 4 As can be seen from the figure, for SiO 2 , with the increase of centrifugation time, the SiO 2 The lubricating oil permeability changes at different levels. Only when SDS and SDBS dispersants were added to the SiO 2 The lubricating oil is relatively stable, and the addition of PVP and sodium citrate, SiO 2 The lubricating oil system is unstable. 3 O 4 ,from Figure 5 It can be seen that the Fe 3 O 4 The lubricating oil permeability increased significantly, indicating that Fe 3 O 4 The precipitation is significant, Fe 3 O 4 The lubricant system is also unstable.

[0057] Therefore, the present invention finally selects nano copper oxide CuO as an additive to prepare lubricating oil, so as to further optimize the effect of the modifier on the thermal conductivity of the nanoparticle lubricating oil.

[0058] Example 1

[0059] This embodiment provides a method for preparing a modified nano copper oxide lubricating oil with high thermal conductivity, specifically:

[0060] 1) Ultrasonic dispersion of nano copper oxide powder in distilled water to obtain a nano copper oxide suspension, wherein the ultrasonic dispersion time of the nano copper oxide is 10 min;

[0061] 2) dissolving γ-methacryloxypropyltrimethoxysilane (KH570) in isopropanol to obtain a KH570 solution, wherein the volume ratio of isopropanol to KH570 is 2:1;

[0062] 3) adding the nano copper oxide suspension to the KH570 solution to obtain a mixed solution, wherein the mass ratio of KH570 to nano copper oxide is 5:1;

[0063] 4) The mixed solution was heated and stirred at 70°C for 30 minutes, and then centrifuged at 9000 rpm for 5 minutes. Then, after washing 3 times, it was dried at 60°C for 16 hours to obtain KH570-modified nano copper oxide powder;

[0064] 5) 0.3 wt % of KH570 modified nano copper oxide powder was added to 30 g of lubricating oil, and ultrasonically dispersed for 10 min, and then magnetically stirred at 900 rpm for 2 h to finally obtain modified copper oxide lubricating oil with high thermal conductivity.

[0065] The morphology of the nano copper oxide used in Example 1 and the modified nano copper oxide prepared was measured, and the results are as follows: Figure 6 shown.

[0066] Figure 6 (a) is the SEM image of unmodified nano copper oxide, and (b) is the SEM image of modified nano copper oxide. It can be seen that the dispersibility of the nano copper oxide particles after modification with KH570 is improved compared with that before modification.

[0067] Fourier transform infrared spectroscopy was performed on the nano copper oxide and KH570 used in Example 1 and the prepared modified nano copper oxide. The results are as follows: Figure 7 shown.

[0068] Figure 7 (1) is the spectrum of KH570, (2) is the spectrum of nano copper oxide modified by KH570, and (3) is the spectrum of unmodified nano copper oxide. It can be seen from the figure that (2) has a peak at 1009 cm -1 ~1320cm -1 The vibration peak of O-Si bond appears between them, at 1172cm -1 The vibration peak of C=O bond appeared at 2892cm -1 and 2979cm -1 The vibration peak of the alkyl group appeared nearby, indicating that the KH570 silane coupling agent successfully modified the surface of nano-copper oxide.

[0069] The nano copper oxide used in Example 1 and the prepared modified nano copper oxide were subjected to X-ray diffraction test, and the results are as follows: Figure 8 shown.

[0070] from Figure 8 It can be seen that compared with pure nano-copper oxide, the XRD pattern of nano-copper oxide modified by KH570 has no obvious change, indicating that the crystal structure of nano-copper oxide has not changed during the surface modification of nano-copper oxide by KH570 silane coupling agent.

[0071] Example 2

[0072] This embodiment provides a method for preparing a modified nano-copper oxide lubricating oil. The mass ratio of KH570 to nano-copper oxide in Example 1 is adjusted to 1:1, and the rest of the preparation process is the same as that in Example 1 to obtain a uniformly dispersed modified nano-copper oxide lubricating oil in this embodiment.

[0073] Example 3

[0074] This embodiment provides a method for preparing a modified nano-copper oxide lubricating oil. The mass ratio of KH570 to nano-copper oxide in Example 1 is adjusted to 2:1, and the remaining preparation processes are the same as those in Example 1 to obtain a uniformly dispersed modified nano-copper oxide lubricating oil in this embodiment.

[0075] Example 4

[0076] This embodiment provides a method for preparing a modified nano-copper oxide lubricating oil. The mass ratio of KH570 to nano-copper oxide in Example 1 is adjusted to 3:1, and the remaining preparation processes are the same as those in Example 1 to obtain a uniformly dispersed modified nano-copper oxide lubricating oil in this embodiment.

[0077] Example 5

[0078] This embodiment provides a method for preparing a modified nano-copper oxide lubricating oil. The mass ratio of KH570 to nano-copper oxide in Example 1 is adjusted to 4:1, and the remaining preparation processes are the same as those in Example 1 to obtain a uniformly dispersed modified nano-copper oxide lubricating oil in this embodiment.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 1 is that the mass ratio of KH570 to nano copper oxide in Example 1 is adjusted to 7:1 and 9:1, and the rest of the preparation process is the same as that in Example 1 to prepare the modified nano copper oxide lubricating oil of this comparative example.

[0081] The KH570 and nano copper oxide used in Comparative Example 1 and the prepared modified nano copper oxide were subjected to Fourier transform infrared testing. The results are as follows: Fig. 9 shown.

[0082] Fig. 9 (1) is the spectrum of nano copper oxide, (2) is the spectrum of KH570, (3) is the spectrum of modified nano copper oxide prepared with a mass ratio of KH570 to nano copper oxide of 7:1, and (4) is the spectrum of modified nano copper oxide prepared with a mass ratio of KH570 to nano copper oxide of 9:1. It can be seen that when the mass ratio of KH570 to nano copper oxide is 7:1 and 9:1, the characteristic peaks of KH570 appear, indicating that the surface of nano copper oxide is successfully modified.

[0083] Thermogravimetric analysis and grafting rate analysis were performed on the nano copper oxide used in Examples 1 to 5 and Comparative Example 1. The results are as follows: Figures 10-11 shown.

[0084] Fig.10(1) to (6) are nano copper oxide and 1g, 2g, 3g, 4g, and 5g of KH570-modified nano copper oxide, respectively, that is, the mass ratio of KH570 to nano copper oxide is 1:1, 2:1, 3:1, 4:1, and 5:1. It can be seen that the slight weight loss of all curves below 140°C is due to the desorption of physically adsorbed water, and in the temperature range of 740°C, the nano copper oxide modified by KH570 loses weight rapidly. As the amount of KH570 added gradually increases to 5g, the weight loss rate gradually decreases, indicating that the surface grafting rate of nano copper oxide continues to increase, and the surface modification effect is getting better and better. At this time, when the mass ratio of KH570 to nano copper oxide is 5:1, the weight loss rate is 78.3%, and the surface grafting rate is 21.7%. The grafting rate is the highest and the modification effect is the best. From Fig.11 It can be seen that when the amount of KH570 added continues to increase, that is, the mass ratio of KH570 to nano-copper oxide increases to 7:1 and 9:1, the surface grafting rate of nano-copper oxide decreases.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is that nano copper oxide that has not been modified by a silane coupling agent is added to the lubricating oil base liquid, and the rest of the preparation process is the same as that of Example 1 to obtain the nano copper oxide lubricating oil of this comparative example.

[0087] The lubricating oils prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested for thermal conductivity at different temperatures. The results are shown in Tables 1 to 2 and Fig.13 shown.

[0088] Table 1 Thermal conductivity of conventional lubricating oil and lubricating oil with different KH570 addition amounts (W / m·K)

[0089]

[0090] It can be seen from Table 1 that the thermal conductivity of pure lubricating oil and nano-copper oxide lubricating oil increases with the increase of temperature. The thermal conductivity of pure lubricating oil is lower than that of lubricating oil with nano-copper oxide added. However, the thermal conductivity of unmodified nano-copper oxide lubricating oil is lower than that of modified nano-copper oxide lubricating oil.

[0091] Depend on Fig.13 It is obvious that during the modification process, as the mass ratio of KH570 modifier to nano copper oxide increases, the thermal conductivity of the lubricating oil first increases and then decreases. When the mass ratio of KH570 to nano copper oxide is 5:1, the thermal conductivity of the lubricating oil is the highest. When the mass ratio of KH570 to nano copper oxide increases to 7:1 and 9:1, the thermal conductivity of the lubricating oil is greatly reduced.

[0092] Table 2 Growth rate of thermal conductivity of lubricating oil with different KH570 additions compared with that of pure lubricating oil

[0093]

[0094] As can be seen from Table 2, with the increase of KH570 mass fraction, the growth rate compared with the thermal conductivity of pure lubricating oil is also increasing. With the increase of temperature, the growth rate of thermal conductivity of lubricating oil with nano copper oxide or modified nano copper oxide is also increasing. Among them, the growth rate of thermal conductivity of lubricating oil with nano copper oxide is the lowest, and its maximum growth rate is only 5.27%, while the growth rate of thermal conductivity of lubricating oil with modified nano copper oxide is relatively high, and its maximum growth rate is 13.32%. When the mass ratio of KH570 to nano copper oxide is 5:1, with the increase of temperature, the growth rate of thermal conductivity of the corresponding lubricating oil compared with the thermal conductivity of pure lubricating oil is the largest.

[0095] Comparative Example 3

[0096] In this comparative example, 0.5 g, 1 g, 3 g, and 5 g of 3-aminopropyltriethoxysilane (APTES) were used to modify nano copper oxide, that is, the mass ratio of APTES to nano copper oxide was 0.5:1, 1:1, 3:1, and 5:1, to prepare APTES-modified nano copper oxide.

[0097] The nano copper oxide used in Comparative Example 3 and the prepared APTES-modified nano copper oxide were subjected to thermogravimetric analysis. The results are as follows: Fig.14 As shown. Fig.14 It can be seen that the thermogravimetric curve of APTES-modified nano-copper oxide conforms to the above-mentioned law of KH570 modification, but the grafting rate is lower than the result of KH570 modification.

[0098] In order to further determine whether the surface modification is successful, the APTES-modified nano-copper oxide prepared at a mass ratio of 5:1 in Comparative Example 3 was subjected to XRD and infrared tests. The results are as follows Figures 15-16 As shown. Fig.15 It can be seen that when the mass ratio of APTES to nano-copper oxide is 5:1, the crystal phase of nano-copper oxide does not change before and after modification, which is consistent with the modification results of KH570. Fig.16 , namely the spectrum of unmodified nano-copper oxide (1), the spectrum of APTES (2) and the spectrum of nano-copper oxide modified with APTES (3). It can be seen that the characteristic peak of APTES does not appear on the surface of modified nano-copper oxide, indicating that APTES has not successfully modified the surface of nano-copper oxide.

[0099] Comparative Example 4

[0100] In this comparative example, KH570 modified nano copper oxide of this comparative example was prepared at 25° C. with a mass ratio of KH570 to nano copper oxide of 1:1 and 2:1 respectively.

[0101] The KH570 modified nano copper oxide prepared in Comparative Example 4 was subjected to thermogravimetric testing. The results are as follows: Fig.17 shown. Fig.17 Among them, (1) is nano copper oxide, (2) is modified nano copper oxide prepared at a mass ratio of KH570 to nano copper oxide of 1:1 at 25°C, and (3) is modified nano copper oxide prepared at a mass ratio of KH570 to nano copper oxide of 2:1 at 25°C. It can be seen from the figure that compared with the nano copper oxide modified at 70°C in Example 1, the nano copper oxide modified at 25°C has a lower grafting rate and a poor modification effect.

[0102] In summary, the modified nano copper oxide prepared by the present invention is not easy to agglomerate in the base liquid and has good dispersion stability. The preparation process of the modified nano copper oxide is simple, the source of the modifier is wide, and the price is low. At the same time, the thermal conductivity of the modified nano copper oxide lubricating oil is higher than that of the unmodified nano copper oxide lubricating oil, which can improve the heat dissipation performance of the lubricating oil of the thrust bearing of the hydro-turbine generator set and effectively control the temperature of the bearing to be not too high. In addition, the nanofluid prepared by using modified copper oxide in the present invention will not cause pollution to the environment and meets the requirements of sustainable development.

[0103] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A modified nano copper oxide lubricating oil with high thermal conductivity, characterized in that: include, Lubricating oil base fluid, and Compared with the nano copper oxide modified by silane coupling agent with the amount of lubricating oil base fluid being 0.05-0.5wt%; Wherein, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the mass ratio of the silane coupling agent to the nano copper oxide is 5 to 1:

1.

2. The modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 1, characterized in that: The mass ratio of the silane coupling agent to the nano copper oxide is 5:

1.

3. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity according to claim 1, characterized in that: include, Nano-copper oxide is ultrasonically dispersed in distilled water to obtain a nano-copper oxide suspension; The silane coupling agent is dissolved in isopropanol to obtain a silane coupling agent solution; The nano copper oxide suspension is added to the silane coupling agent solution to obtain a mixed solution, and the mixed solution is heated, stirred, centrifuged, washed, and dried to obtain nano copper oxide powder modified by the silane coupling agent; The nano copper oxide powder modified by silane coupling agent is added into the lubricating oil base liquid, and the modified nano copper oxide lubricating oil with high thermal conductivity is obtained through ultrasonic dispersion and magnetic stirring.

4. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The heating and stirring temperature of the mixed solution is 60-80° C., and the stirring time is 30-50 min.

5. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The mixed solution is centrifuged at a speed of 5000 to 9000 rpm for 5 to 15 minutes.

6. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The washing is performed 3 to 5 times.

7. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The drying temperature is 60-80° C., and the drying time is 16-24 hours.

8. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The ultrasonic dispersion time is 10 to 15 minutes.

9. The method for preparing the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 2, characterized in that: The rotation speed of the magnetic stirring is 900-1000 rpm, and the time of the magnetic stirring is 2-4 hours.

10. Use of the modified nano copper oxide lubricating oil with high thermal conductivity as claimed in claim 1 in a thrust bearing of a hydro-generator.